The Impact of Sound System Event Implementation and Visit Intensity on the Income of Micro, Small, and Medium Enterprises (MSMEs) - Syarofi, Muhammad; Nurhaliza; Hakim, Faris Kurnia; Firdaus, Cecep Bryan (Faculty of Islamic Economics and Business, Madura Islamic State University, 2025)
This study aims to analyze the influence of sound system event attendance and visit intensity on the increase in income of Micro, Small, and Medium Enterprises (MSMEs) in Padomasan Village. This research employs a quantitative approach using a survey method, with data analysis conducted through the Structural Equation Modeling–Partial Least Squares (SEM-PLS) technique using SmartPLS software. Data were collected through questionnaires distributed to several MSME respondents in Padomasan Village. The results of this study indicate that both the presence of sound system events and the intensity of visits have a positive and significant influence on the increase in MSME income in Padomasan Village. Sound system events can serve as a major attraction for visitors, increasing the number of buyers and thereby having a positive impact on MSME income. In addition, a high level of visit intensity also contributes to the growth of MSME product sales. The presence of sound system events and the frequency of visits are important factors that need to be considered in efforts to increase the income of MSMEs in Padomasan Village.